2021
DOI: 10.1007/s10549-021-06394-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of use of oral complementary-alternative medicine among women with early breast cancer: a focus on cancer-related fatigue

Abstract: BACKGROUND: Despite the questionable effectiveness of oral complementary and alternative medicine (OCAM) in relieving cancer-related symptoms, including fatigue (CRF), many patients use it aiming to improve their quality of life.We assessed factors associated with OCAM use, focusing on CRF. METHODS:Women with stage I-III breast cancer (BC) were included from CANTO (NCT01993498). OCAM use was defined as taking homeopathy, vitamins/minerals or herbal/dietary supplements. Multivariable multinomial logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…At this time, there are many studies that examine the effect of dietary supplements, such as probiotics [ 46 , 47 ], B-complex multivitamin/mineral supplementation [ 48 ], magnesium [ 49 ], and omega-3 [ 50 ] for anxiety, but there are few reports on whether anxiety towards health encourages people to use dietary supplements. Anxiety was associated with dietary supplement/complementary alternative medicine in cancer survivors [ 51 ], women with early breast cancer [ 52 ], and patients with liver disease [ 53 ] but not healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, there are many studies that examine the effect of dietary supplements, such as probiotics [ 46 , 47 ], B-complex multivitamin/mineral supplementation [ 48 ], magnesium [ 49 ], and omega-3 [ 50 ] for anxiety, but there are few reports on whether anxiety towards health encourages people to use dietary supplements. Anxiety was associated with dietary supplement/complementary alternative medicine in cancer survivors [ 51 ], women with early breast cancer [ 52 ], and patients with liver disease [ 53 ] but not healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, a longitudinal study among colorectal cancer survivors showed no differences in fatigue between dietary supplement users (predominately multivitamins) and nonusers [ 108 ]. In contrast, the use of oral complementary and alternative medicine (OCAM), defined as taking homeopathy, vitamins/minerals, or herbal/dietary supplements, was associated with more severe CRF in stage I–III breast cancer survivors [ 110 ].…”
Section: Dietary Recommendations For Cancer-related Fatiguementioning
confidence: 99%
“…In fact, at least 43% of patients take nutritional supplements during treatment, despite evidence that some supplements (e.g., antioxidants) are associated with an increased risk of recurrence and poorer survival [ 14 ]. Moreover, “oral complementary and alternative medicine,” defined as taking homeopathy, vitamins/minerals, herbal supplements, or other dietary supplements, was associated with worse cancer-related fatigue during cancer treatment [ 15 ]. Other pleiotropic behavioral interventions such as exercise and cognitive behavioral therapy are the most effective interventions available to combat cancer-related fatigue and are more effective than available pharmaceutical interventions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%